Animal-based food choice and associations with long-term weight maintenance and metabolic health after a large and rapid weight loss: The PREVIEW study. Issue 4 (April 2022) - Zhu, Ruixin; Fogelholm, Mikael; Jalo, Elli; Poppitt, Sally D.; Silvestre, Marta P.; Møller, Grith; Huttunen-Lenz, Maija; Stratton, Gareth; Sundvall, Jouko; Macdonald, Ian A.; Handjieva-Darlenska, Teodora; Handjiev, Svetoslav; et al.
Summary: Background & aims: Low-energy diet replacement is an effective tool to induce large and rapid weight loss and improve metabolic health, but in the long-term individuals often experience significant weight regain. Little is known about the role of animal-based foods in weight maintenance and metabolic health. We aimed to examine longitudinal associations of animal-based foods with weight maintenance and glycaemic and cardiometabolic risk factors. We also modelled replacement of processed meat with other high-protein foods. Methods: In this secondary analysis, longitudinal data were analysed from 688 adults (26–70 years) with overweight and prediabetes after 8-week low-energy diet-induced weight loss (≥8% of initial body weight) in a 3-year, multi-centre, diabetes prevention study (PREVIEW). Animal-based food consumption, including unprocessed red meat, processed red meat, poultry, dairy products, fish and seafood, and eggs, was repeatedly assessed using 4-day food records. Multi-adjusted linear mixed models and isoenergetic substitution models were used to examine the potential associations. Results: The available-case analysis showed that each 10-g increment in processed meat, but not total meat, unprocessed red meat, poultry, dairy products, or eggs, was positively associated with weight regain (0.17 kg⋅year −1, 95% CI 0.10, 0.25, P  < 0.001) and increments in waist circumference, HbA1c, and triacylglycerols. The associations of processed meat with HbA1c or triacylglycerols disappeared when adjusted for weight change. Fish and seafood consumption was inversely associated with triacylglycerols and triacylglycerol-glucose index, independent of weight change. Modelled replacement of processed meat with isoenergetic (250–300 kJ·day −1 or 60–72 kcal·day −1 ) dairy, poultry, fish and seafood, grains, or nuts was associated with −0.59 (95% CI -0.77,  −0.41),  −0.66 (95% CI -0.93,  −0.40),  −0.58 (95% CI -0.88,  −0.27), and −0.69 (95% CI -0.96,  −0.41) kg·year −1 of weight regain, respectively (all P  < 0.001) and significant improvements in HbA1c, and triacylglycerols. Conclusions: Higher intake of processed meat, but not total or unprocessed red meat, poultry, dairy products, or eggs may be associated with greater weight regain and more adverse glycaemic and cardiometabolic risk factors. Replacing processed meat with a wide variety of high-protein foods, including unprocessed red meat, poultry, dairy products, fish, eggs, grains, and nuts, could improve weight maintenance and metabolic health after rapid weight loss. This study was registered as ClinicalTrials.gov, NCT01777893.